2017
DOI: 10.1007/s10654-017-0340-1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age at birth and risk of intellectual disability without a common genetic cause

Abstract: Preterm birth is linked to intellectual disability and there is evidence to suggest post-term birth may also incur risk. However, these associations have not yet been investigated in the absence of common genetic causes of intellectual disability, where risk associated with late delivery may be preventable. We therefore aimed to examine risk of intellectual disability without a common genetic cause across the entire range of gestation, using a matched-sibling design to account for unmeasured confounding by sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 62 publications
10
44
0
Order By: Relevance
“…The risk of intellectual disability increases exponentially as gestational age decreases in preterm children [11,12]. A similar trend of increasing risk by decreasing gestational age was recently shown in children born at term (37-41 weeks), whereas a trend of increasing risk by increasing gestational age was observed in children born post-term (≥ 42 weeks) [12]. The same study also suggested a joint impact of term or postterm birth and SGA versus term birth and AGA.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The risk of intellectual disability increases exponentially as gestational age decreases in preterm children [11,12]. A similar trend of increasing risk by decreasing gestational age was recently shown in children born at term (37-41 weeks), whereas a trend of increasing risk by increasing gestational age was observed in children born post-term (≥ 42 weeks) [12]. The same study also suggested a joint impact of term or postterm birth and SGA versus term birth and AGA.…”
Section: Introductionsupporting
confidence: 70%
“…Preterm birth (< 37 gestational weeks) is another known risk factor for cognitive deficits [10]. The risk of intellectual disability increases exponentially as gestational age decreases in preterm children [11,12]. A similar trend of increasing risk by decreasing gestational age was recently shown in children born at term (37-41 weeks), whereas a trend of increasing risk by increasing gestational age was observed in children born post-term (≥ 42 weeks) [12].…”
Section: Introductionmentioning
confidence: 67%
“…Changes in the overall magnitude of neonatal cell death may lead to long-term changes in neuron number, as shown for effects of birth mode in mice (Castillo-Ruiz et al, 2018b). Because naturally-occurring cell death in the human brain is ongoing at birth (Lossi et al, 1998;Abrahám et al, 2001;Lavezzi et al, 2006;Abitz et al, 2007), it is possible that some of the reported effects of birth timing on child development (El Marroun et al, 2012;Abel et al, 2017;Heuvelman et al, 2018) are related to alterations in cell death, or a dissociation of cell death from other neurodevelopmental events…”
Section: Discussionmentioning
confidence: 99%
“…However, globally, complications related to preterm birth remain a major cause of neonatal and under‐5 mortality (Liu et al., ). Preterm individuals also are at substantially higher risk of impairments affecting multiple organ systems (Haraldsdottir et al., ; Huang, Lin, Wang, Su, & Lin, ; Parkinson, Hyde, Gale, Santhakumaran, & Modi, ), including potentially disabling neurological and neuropsychiatric disorders (Agrawal, Rao, Bulsara, & Patole, ; Franz et al., ; Heuvelman et al., ; Nosarti et al., ; Sutton & Darmstadt, ). This highlights the importance of determining the mechanisms behind preterm birth and how these mechanisms might relate to the difficulties faced later in life.…”
Section: Introductionmentioning
confidence: 99%
“…The former is where labor is induced or a Caesarean section is performed because of medical risks or complications, the latter where onset of labor occurs spontaneously prior to 37 weeks gestation. However, this distinction fails to take into impairments affecting multiple organ systems (Haraldsdottir et al, 2018;Huang, Lin, Wang, Su, & Lin, 2018;Parkinson, Hyde, Gale, Santhakumaran, & Modi, 2013), including potentially disabling neurological and neuropsychiatric disorders (Agrawal, Rao, Bulsara, & Patole, 2018;Franz et al, 2018;Heuvelman et al, 2018;Nosarti et al, 2012;Sutton & Darmstadt, 2013). This highlights the importance of determining the mechanisms behind preterm birth and how these mechanisms might relate to the difficulties faced later in life.…”
Section: Introductionmentioning
confidence: 99%